Apakah RTH Bumirejo Pudakpayung Kota Semarang Sudah Memenuhi Kriteria SDGs? - Pangarso, R Agung (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
SDGs are the blueprint to achieve a better and more sustainable future for all. Goal #11 target #11.7 â€œProvide access to safe and inclusive green and public spacesâ€ means that by 2030, cities should provide universal access to safe, inclusive, and accessible, green, and public spaces, for women and children, older persons, and persons with disabilities. This research was conducted at the Bumirejo green public space in Semarang, which provides facilities for recreation, social interaction, sports, and playground for the community. This research aims to determine if the elements of the Bumirejo green public space met the SDGs criteria. This research was conducted with a qualitative and quantitative approach. Analysis determined how the green public spaces meet the following criteria: a. Inclusive (facility for all); b. Adequate accessibility c. Attractive amenities; d. Comfortable, safe, and healthy; and e. Natural green environment. The results of the analysis showed that some elements of Bumirejo green public space are still poor in terms of inclusiveness and accessibility. This weakness can be seen at the elements of the main entrance, stairs, and pedestrian paths. In these elements, there is no access to wheelchairs, ramps, and blind paths, which means persons with disabilities are unable to use this facility. These green public space elements are not attractive such as stairs, parking areas, soccer fields, open stage, and pedestrian paths. Generally, these elements are not well designed regarding architectural standards. Analysis also found uncomfortable and unsafe elements such as too narrow stairs and pedestrian paths that are not designed according to architectural standards. This research concludes that several elements of Bumirejo green public space have not met the SDGs criteria in terms of inclusiveness, accessibility, attractiveness, comfort, and safety. This research recommends improvements particularly at the main entrance, stairs, and pedestrian paths to be able to access wheelchair paths, providing ramps and blind paths. The pedestrian paths surrounding the soccer field need to be widened. Improvements to make this facility more attractive particularly at the parking area, soccer field, and open stage. All improvement should be regarding the architectural principles and standards.